Wittgenstein’s Language Game and Musical Language (of The Second Viennese School) – Meaning and Understanding - Milica Lazarević (AM: Art + Media, 2016)
The three fundamental and closely-related concepts from Wittgenstein’s late work Philosophical Investigation – the concept of language game, of meaning and of understanding – are exemined in this study in the context of the problematization of music as a musical language and a musical language/piece of music (used in the traditional European sense) as a musical-language game, as well as the questions of its meaning and understanding. In connection with this, the period of radical changes in the traditional tonal musical language in the compositions of The Second Viennese School turned out to be peculiarly provocative, hence, on this occasion, we are attempting to point out the specificities of the changes of a (musical) language built and upgraded through the centuries.